Monitoring Electrochemical Degradation of Concrete Structures - S.D. Brito, Paulo; Romano, Pedro (Recent Patents on Corrosion Science, 2013)
This paper intends to review the main systems of monitoring the degradation of reinforced concrete structures with steel that have been patented in the last 10 years. Given that the degradation process in the large majority of cases is an electrochemical corrosion process of the reinforcement caused by chemical actions on the structure, the systems are generally systems that determine electrochemical greatnesses. The systems are essentially sets of electrodes with different arrays that allow the implementation of different electrochemical techniques such as linear polarization resistance, electrochemical impedance spectroscopy, electrochemical noise, ionic conductivity, in order to obtain information about reinforcement potentials and corrosion rates and penetration speeds of aggressive agents.
Keywords: Electrochemical monitoring